O desenvolvimento psicoafetivo: a relação mãe-filho e o contexto social - Giffoni, Francinete Alves de Oliveira (1999)
The present essay concerns to the Human Development, in its psychological and affective aspects, on the basis of family relationships and interation bettween the constitutional factors and the social contexto. In that approach we tryed to demonstrate the influence of the social and historical relations, defined since the starting phases of the developing processo. Also, it looks to draw the personality by developing the psycological, affective and cognitive dimensions of the self.